Differential expression and evolutionary diversification of RNA helicases in Boechera sexual and apomictic reproduction - Binmöller, Laura; Volkert, Christopher; Kiefer, Christiane; Zühl, Luise; Slawinska, Magdalena W.; Loreth, Anna; Nauerth, Berit H.; Ibberson, David; Martinez-Gallegos, Rafael; Mandakova, Terezie M.; Zipper, Reinhard; Schmidt, Anja (The journal of experimental botany, 2024)
In higher plants, sexual reproduction is characterized by meiosis of the first cells of the germlines, and double fertilization of the egg and central cell after gametogenesis. In contrast, in apomicts of the genus Boechera, meiosis is omitted or altered and only the central cell requires fertilization, while the embryo forms parthenogenetically from the egg cell. To deepen the understanding of the transcriptional basis underlying these differences, we applied RNA-seq to compare expression in reproductive tissues of different Boechera accessions. This confirmed previous evidence of an enrichment of RNA helicases in plant germlines. Furthermore, few RNA helicases were differentially expressed in female reproductive ovule tissues harboring mature gametophytes from apomictic and sexual accessions. For some of these genes, we further found evidence for a complex recent evolutionary history. This included a homolog of Arabidopsis thaliana FASCIATED STEM4 (FAS4). In contrast to AtFAS4, which is a single-copy gene, FAS4 is represented by three homologs in Boechera, suggesting a potential for subfunctionalization to modulate reproductive development. To gain first insights into functional roles of FAS4, we studied Arabidopsis lines carrying mutant alleles. This identified the crucial importance of AtFAS4 for reproduction, as we observed developmental defects and arrest during male and female gametogenesis.